2011
DOI: 10.1121/1.3641401
|View full text |Cite
|
Sign up to set email alerts
|

Combined spectral and temporal enhancement to improve cochlear-implant speech perception

Abstract: The present study examined the effect of combined spectral and temporal enhancement on speech recognition by cochlear-implant (CI) users in quiet and in noise. The spectral enhancement was achieved by expanding the short-term Fourier amplitudes in the input signal. Additionally, a variation of the Transient Emphasis Spectral Maxima (TESM) strategy was applied to enhance the short-duration consonant cues that are otherwise suppressed when processed with spectral expansion. Nine CI users were tested on phoneme r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…Some approaches are based on fairly basic forms of signal processing such as high-pass filtering followed by amplitude compression (Niederjohn and Grotelueschen, 1976), or signal-to-noise ratio (SNR) recovery (Sauert and Vary, 2006). Spectral contrast enhancement has been used as a possible method of compensating for the reduced frequency selectivity of hearing-impaired people (Baer et al, 1993;Oxenham et al, 2007;Bhattacharya et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Some approaches are based on fairly basic forms of signal processing such as high-pass filtering followed by amplitude compression (Niederjohn and Grotelueschen, 1976), or signal-to-noise ratio (SNR) recovery (Sauert and Vary, 2006). Spectral contrast enhancement has been used as a possible method of compensating for the reduced frequency selectivity of hearing-impaired people (Baer et al, 1993;Oxenham et al, 2007;Bhattacharya et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…While the TESM strategy showed a significant improvement of 11.3% at an SNR of 5 dB in multitalker babble noise (Vandali, 2001), the same strategy did not differ significantly in a sentence recognition task in Holden et al (2005) when the target signal level was presented at 65 dB SPL. Bhattacharya et al (2011) even observed a decrease in speech intelligibility in quiet for the strategy and obtained a significant improvement when adding an additional spectral extension stage to the processing. The TESM strategy is more focused on the transient part and not the onset of the speech envelope.…”
Section: Discussionmentioning
confidence: 99%
“…Vandali (2001) developed the transient emphasis spectral maxima (TESM) strategy that amplifies transient parts of the signal with a gain factor derived from a comparison of the averaged energy in three consecutive time windows in each processing channel. In several studies with CI listeners ( Vandali, 2001;Bhattacharya et al, 2011), it was shown that small but significant improvements in speech intelligibility were obtained with the TESM strategy in quiet for consonant recognition and in multitalker babble noise at 5 dB SNR (Vandali, 2001) or in combination with a spectral expansion stage (Bhattacharya et al, 2011). In contrast, Holden et al (2005) found no increase in speech intelligibility with this strategy.…”
Section: Introductionmentioning
confidence: 89%
“…In contrast to vowels, the acoustic information associated with consonants tends to be more rapidly changing and related to formant transitions and other acoustic characteristics that would require fairly good auditory resolution of rapidly changing spectral information. Research exploring the relationship between the ability to perceive temporal and spectral modulation and speech perception suggests that these abilities are related and that limited modulation resolution may play a role in speech perception (Bhattacharya et al 2011;Won et al 2011), particularly for consonant perception (Van Tasell et al 1987).…”
Section: Table 5 Correlations Of the Mean Scores On Perception And Pmentioning
confidence: 98%